Crop-livestock-forest integration systems: A scientometric analysis - Silva, Hérica André da; Santos, Leovigildo Aparecido Costa; Pacheco, Abílio Rodrigues; Calil, Francine Neves; Silva-Neto, Carlos de Melo e (Revista Ecologia e Nutrição Florestal - ENFLO, 2021)
Scientometrics studies a specific discipline of science through quantitative indicators. Integrated production systems are a scientific knowledge area aimed at developing sustainable rural production. These systems require adequate and thorough planning of agricultural, forestry and livestock components in order to adequately protect natural resources. Scientometric studies help to quantitatively analyze these studies and generate more accurate instruments to formulate and adopt public and scientific policies. The objective of this work was to carry out a scientometric analysis of knowledge production for crop-livestock-forest integration (CLFI) systems worldwide, in order to identify the following: (a) the most productive authors; (b) the historical evolution of the number of publications and journals that publish the most on the topic; (c) the countries that produce the most scientific knowledge on the topic; and (d) the main approaches that cover the topic. A total of 1,592 studies were retrieved from the Web of Science and Scopus databases, covering the period from 1983 to August 2020. Brazil had the largest number of publications on crop-livestock-forest integration systems. Most articles were characterized in the sustainability, biodiversity and conservation knowledge areas. Our results indicate that scientific efforts have been devoted to studies related to sustainable production practices and integrated systems have been pointed out as a potential production system that meets the current demands for sustainable development, especially in tropical developing countries.